Tiempo de calabazas! - Hall, Zoe, 1957-; Halpern, Shari; Fabiancic, Miriam (New York : Scholastic, 2000)
A sister and brother plant and tend their own pumpkin patch so they will have jack-o-lanterns for Halloween.
Keywords: Pumpkin -- Fiction; Halloween -- Fiction; Jack-o-lanterns -- Fiction; Spanish language materials -- Fiction; Picture books